Large-scale mechanical peeling of boron nitride nanosheets by low-energy ball milling - ZHANG, HONGZHOU (My University, 2011)
Mechanical cleavage by Scotch tape was the first method to produce graphene and is still widely used in laboratories. However, a critical problem of this method is the extremely low yield. We have tailored ball milling conditions to produce gentle shear forces that produce high quality boron nitride (BN) nanosheets in high yield and efficiency. The in-plane structure of the BN nanosheets has not been damaged as shown by near edge X-ray absorption fine structure measurements. The benzyl benzoate acts as the milling agent to reduce the ball impacts and milling contamination. This method is applicable to any layered materials for producing nanosheets.
PUBLISHED
Keywords: Scotch tape; Nanoscience & Materials